(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article is aimed at studying the impact of an international language, which is becoming popular nowadays, on the knowledge of the English language. The article also focuses on the study of vocabulary and language skills: speaking, reading and writing, and we consider the effect of several elements of social media on each. From the results of this study, we can safely say that social media has more influence on our writing skills than any other skills. Advanced software can turn any large message into a simple game. The reason is that our smartphones have become smarter than our spoken conversation. For example, the basic building blocks of any language lie in its roots and sentence structures. Similar conversational processes are replaced or modified on smartphones by introducing several elements such as abbreviations, emoticons, and auto-completion. This article examines the positive and negative aspects of the influence of the media on the language and makes a critical assessment.